2018
DOI: 10.20471/acc.2018.57.03.02
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Level of Malondialdehyde and Progression of Colorectal Cancer

Abstract: SUMMARY – The purpose of the study was to assess the level of serum malondialdehyde (MDA) concentration and its association with the stage and histopathologic sizes of colorectal cancer (CRC). One hundred and two patients having undergone surgical treatment of CRC between January 2014 and December 2015 were included in this cross-sectional study. The patients were divided into four groups (stage I-IV) according to the TNM classification. Control group included 30 subjects with no signs of malignancy and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Rašić et al noted similar results. Their study demonstrated statistically significant differences in serum MDA levels and stage II and III of the disease (p < 0.01) [20]. However, Wu et al observed no statistically significant differences in TOS and TAS levels and the clinical stage of the cancer (p < 0.05) [15].…”
Section: Discussionmentioning
confidence: 90%
“…Rašić et al noted similar results. Their study demonstrated statistically significant differences in serum MDA levels and stage II and III of the disease (p < 0.01) [20]. However, Wu et al observed no statistically significant differences in TOS and TAS levels and the clinical stage of the cancer (p < 0.05) [15].…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, lipid peroxidation is enhanced with the increase in the depth of tumour invasion. It is suggested that MDA can act as a carcinogenic agent and promoter of CRC development/progression [ 53 ]. This is also confirmed by higher MDA level in patients with high-grade tumour budding as well as in subjects with lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ROS-related tissue destruction can be observed by the final products of lipid peroxidation, such as MDA. Therefore, MDA’s diagnostic utility has been suggested in many diseases, such as colorectal cancer 42 , spontaneous intracerebral hemorrhage 43 , depression 44 , 45 , and alcoholic hepatitis diagnosis 46 . Furthermore, MDA has also been demonstrated to be a significant independent positive predictor of the patient depth of tumor invasion and an independent positive predictor of lymph node infiltration by cancer tissue, as well as the occurrence of metastasis 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MDA’s diagnostic utility has been suggested in many diseases, such as colorectal cancer 42 , spontaneous intracerebral hemorrhage 43 , depression 44 , 45 , and alcoholic hepatitis diagnosis 46 . Furthermore, MDA has also been demonstrated to be a significant independent positive predictor of the patient depth of tumor invasion and an independent positive predictor of lymph node infiltration by cancer tissue, as well as the occurrence of metastasis 42 . However, when considering common MDA measurements in clinical practice, the need for full validation data should be considered.…”
Section: Discussionmentioning
confidence: 99%